Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan - Dhiva Ayu Arzrial Azzha; Susantiningrum Susantiningrum; Nur Rahmi Akbarini (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine (1) the effect of leadership style variable on employee performance PT. Assalaam Niaga Utama; (2) the effect of work environment variable on employee performance PT. Assalaam Niaga Utama; (3) the effect of leadership style and work environment partially and simultaneously on employee performance PT. Assalaam Niaga Utama. The population in this research was all employee of PT. Assalaam Niaga Utama as many as 154 employees with 62 employees are used research sample. This research used proportionate stratified random sampling technique to find the research sample. The research method used the correlational quantitative method with data collection techniques used questionnaires. Data analysis techniques used multiple linear regression analysis techniques with software IBM SPSS20.0 program for window. The result of the analysis show that’s leadership style and work environment has positive and significant simultaneously of employee performance of 37,3% with the value of Fhitung (17,584) > Ftabel (3,15). Leadership style has positive and significant of employee performance with the value of thitung (2,564) > ttabel (2,001). Work environment has positive and significant of employee performance with the value of thitung (2,263) > ttabel (2,001).